Assessment of current state of Modernist building heritage of Skopje in terms of sustainability, energy efficiency and authentic appearance degradation - Dimevska Liljana; Cvetkovska Meri; Trombeva Gavriloska Ana; Lazarevska Marijana; Knezevic Milos (IOP Publishing, 2020)
Skopje has unique examples of modernist architecture that play a major role in creating the new identity of the city, which was completely lost after the earthquake in 1963. In the last decade, awareness has been raised that modernist buildings deserve to be protected as cultural monuments. On the other hand, concerning energy efficiency and sustainability aspect, they were built without thermal insulation and thus have extremely poor thermal properties. In order to improve the energy efficiency, retrofit interventions are constantly being implemented and their authentic appearance have been changed. Many buildings have already been changed to an unrecognizable stile which threatens the overall architectural identity of the city. Therefore, systematic research has been done on 50 valuable buildings from the period of Modernism in Skopje. The buildings are selected according to their architectural, structural and cultural historical values. They are analysed from following aspects: construction, building materials, thermal properties, function, cultural heritage protection, level of authenticity degradation, preservation and retrofit measures. The purpose of this paper is to define the most common types of buildings, which are in same time the most problematic in terms of energy efficiency, sustainability and authentic appearance.